Radiographic localisation of the entheses of the equine stifle. (31st August 2016) - Aldrich, E. D.; Goodrich, L. R.; Monahan, M. K.; Conway, J. D.; Valdés‐Martínez, A.
Summary: Reason for performing study: Injury to the tendons and ligaments of the equine stifle is a common cause of lameness in horses. Individual radiographic localisation of each tendon and ligament of the stifle has not been previously reported or demonstrated in multiple radiographic projections. Objective: To create a series of radiographs identifying the origins and/or insertions of the tendons and ligaments of the equine stifle. Study design: Descriptive study of radiographic anatomy. Methods: The location of all entheses were determined by gross dissection. The proximal tibia and fibula, distal femur, patella and menisci were isolated from one horse and used as a template. A series of 4 radiographs was obtained with each enthesis identified with barium paste. The radiographic landmarks for each enthesis were described and the best projection(s) for evaluation of each structure of interest identified. Results: Forty‐eight radiographic images were produced that demonstrated the best radiographic projections to define each enthesis. Conclusions: Radiography is the imaging modality most frequently used to evaluate the equine stifle. The images presented here will serve as a guide for evaluating radiographs of the equine stifle, particularly identifying avulsions and enthesopathies of ligamentous and tendinous origins and insertions.